Travel selfies on social networks, narcissism and the “attraction-shading effect” - Christou, Prokopis A.; Farmaki, Anna; Saveriades, Alexis; Georgiou, Marios (My University, 2020)
This paper aims to trigger researchers' intuitiveness on the somewhat overlooked construct of narcissism from a tourism perspective. The study investigates whether tourists’ self-presentation at destinations excludes sites from the picture, thus underpinning a manifestation of narcissism. Anchored in 52 interviews conducted with tourists, the findings show that there is a tendency to capture oneself (or mostly oneself) in a travel selfie while excluding destination attributes or shifting them to the side of the photograph. This action causes an “attraction-shading effect”, with destinations facing the challenge of having their sites illustrated in travel photographs shared on social networks. The paper invites scholars to use the tourism context to delve deeper into the notion of narcissism and its impacts at a destination and societal level.
Keywords: Selfies; Pictures; Narcissism; Destination